KOMPLEKSITAS PENGELOLAAN KAWASAN BENTENG VREDEBURG YOGYAKARTA - Niken Wirasanti (BRIN, 2009)
The development and modification of a city is an unavoidable process. However, to preserve the identity of a city is a necessity; for instance, city of Indonesian struggle for freedom, and city of culture heritage. All have been characterized with icons available throughout Yogyakarta area. The identities of Yogya as a City of Indonesian struggle for freedom and City of Culture heritage, among others, are reflected at the Benteng Vredeburg Museum and is surrounding. But at the same time various hotels and shopping mall are built nearby the site. Even though Government regulation on environmental management (Environmental Impact Analysis) have been made, however, at that location, the Cultural Heritage sites, one by one, have been destroyed and replaced by modern buildings.